Knowledge on Goitre: a comparison between remote inland and coastal areas - Zaleha Md. Isa; Osman Ali; Khalid Abdul Kadir (Universiti Kebangsaan Malaysia, 1995)
Please refer fulltext/Sila rujuk teks penuh